(3OjhGf GdYUahQjs - (3eMeO Hf CHj HcQ GdYUahQj,J (B1103 (3g` s
(3ChdgG (B:s
(3MeOkG def CWdY KeGQ GdBOGH Ydi CaJGf GdCdSfI GdYQHjI bGajI GdCda(B: (3CdG ef GdOGA aj CYLRg GdHQA hOeY hMj GdScH CYhRg GdQbA s
(3BNQgG (B:s
(3bUjOI jGFjI JfJgj Hbhdg(B: (3dbO JQcJ GdbWG djdG afGe hdh CgLJg dSYi SYj GdbWGej s
(3eQJH Ydi MQha GdeYLes
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B2 - (3U (B42s
(3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA (B1 - (3bSe (B3 - (3U (B157 s
(3JHUQGJ GdCUd (B:s
(3GdfSNI HNW GdeDdas
Keywords: (3GdCOHs